The Effect Of Cricket Flour Addition (Acheta Domesticus) In Feed On Production Performance Of Quail (Cortunix Cortunix Japonica) - Bagus Andika Fitroh; Adib Norma Respati; Putri Awaliya Dughita (Bantara Journal of Animal Science, 2020)
The purpose of this research was to study the effect of cricket flour addition on production performance of quail including: feed consumption, egg production, and feed convertion. There were 240 female of quail  selected at 47 days of age which were divided into four treatments including: 100 % of basal feed (P0), 95% of basal feed + 5% of  cricket flour (P1) , 90% of basal feed + 10% of cricket flour (P2), 85% of basal feed + 15% of cricket flour (P3). The research method used was experiment using completely random design. The obtained data were analyzed by Anova (Analysis of variance), if there was significant different it would be tested by Duncan's Multipel range test (DMRT). The results of this research showed that the addition of cricket flour on feed give a significantly different on (P<0.01) feed consumption, egg production, and feed conversion. The highest to the lowest of feed consumption was T3 (23.83 ± 0.09d), T2 (23.62 ± 0.05c ), T1 (23.41 ± 0.11b), T0 (23.21 ± 0.08a); the highest to the lowest of HDP was T3 (91.01 ± 2.09c), T2 (87.68 ± 3.06b), T1(86.13 ± 5.51b), T0 (79.71 ± 4.58a); the highest to the lowest of egg mass was T3 (8.65 ± 0.20b), T2(8.33 ± 0.29b), T1 (8.19 ± 0.52b), T0(7.57 ± 0.44a); the highest to the lowest of feed conversion was T0 (3.09 ± 0.19c), T1(2.89 ± 0.19b), T2 (2.85 ± 0.10ab), T3 (2.76 ± 0.06a). The conclusions of this research was that the addition of cricket flour in feed can improve performance production of quail. The best treatment was T3 with the addition of 15% cricket flour in feed it is advisable toget the best results should be used cricket flour respectively15% in feed and used basal feed in mash to feed can be mixed perfectly with cricket flour. Keywords : cricket flour, quail, quail performance.